1974
DOI: 10.1007/bf00388268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytochrome on development of catalase activity and isoenzyme pattern in mustard (Sinapis alba L.) seedlings

Abstract: In contrast to an earlier publication (Drumm et al., Cytobiol. 2, 335, 1970), a definite enhancement by phytochrome of the catalase level in mustard (Sinapis alba L.) cotyledons can be demonstrated. This response can be obtained either with continuous far-red light or with short red pulses, the effect of which is reversible by short far-red pulses. From the comparison of the time courses of catalase activity with the time courses of glyoxysomal (isocitrate lyase) and peroxisomal (glycolate oxidase, glyoxylate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
2
2

Year Published

1975
1975
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 31 publications
2
29
2
2
Order By: Relevance
“…A previous study on catalase indicated that during the transition, the three-band isozyme pattern on electrophoresis is supplemented by an additional nine bands (3). By contrast, evidence is presented here that the microbody MDH isozyme is not altered during the transition in microbody function.…”
contrasting
confidence: 65%
“…A previous study on catalase indicated that during the transition, the three-band isozyme pattern on electrophoresis is supplemented by an additional nine bands (3). By contrast, evidence is presented here that the microbody MDH isozyme is not altered during the transition in microbody function.…”
contrasting
confidence: 65%
“…Vol. 112, 1996 mustard (Drumm and Schopfer, 1974). Small families of catalase genes have been described for castor bean (Suzuki et al, 1994), N. plumbaginifolia (Willekens et al, 1994a(Willekens et al, , 1994b, and maize (Scandalios, 1987(Scandalios, , 1990.…”
mentioning
confidence: 99%
“…In each case the authors addressed the problem of the number of microbody types involved in their systems, but could not draw definitive conclusions based on the data. Drumm and Schopfer (3) believe their comparison of the time course of catalase activity with time courses of glyoxysomal and peroxisomal enzymes in dark-grown and far red-irradiated watermelon cotyledons provides further circumstantial evidence favoring the microbody transformation hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Their data are most consistent with the concept ot succession within existing particles (models 2 and 3). Definitive data are not available to determine whether peroxisomal enzymes are located in nonfunctional particles at the time of glyoxysomal metabolism (model 2) or in the same particles that house glyoxysomal enzymes (model 3).…”
Section: Discussionmentioning
confidence: 99%